2006
DOI: 10.1051/0004-6361:20054218
|View full text |Cite
|
Sign up to set email alerts
|

3D spectroscopy with VLT/GIRAFFE

Abstract: Luminous Compact Galaxies (LCGs) are enigmatic sources in many aspects. They can reach the luminosity of the Milky Way within a radius of only a few kpc. They also represent one of the most rapidly evolving populations of galaxies since they represent up to 1/5 of the luminous galaxies at redshift z = 0.7, while being almost absent in the local Universe. The measurement of their dynamics is crucial to our understanding of LCGs since this has the potential of telling us which physical process(es) drive(s) them … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 42 publications
1
79
1
Order By: Relevance
“…Law et al, 2009, and references therein) whose origin is still highly debated. Among other mechanisms, mergers (Puech et al, 2006(Puech et al, , 2007 and massive star formation (Lehnert et al, 2009) have been proposed. Förster-Schreiber et al (2009) conclude from galaxies in the SINS survey that around 30% of the galaxies at z=1-3 are rotationally supported, but turbulent disks probably indicate they have completed most of their formation process, while another 30% might be galaxy mergers.…”
Section: Kinematicsmentioning
confidence: 99%
“…Law et al, 2009, and references therein) whose origin is still highly debated. Among other mechanisms, mergers (Puech et al, 2006(Puech et al, , 2007 and massive star formation (Lehnert et al, 2009) have been proposed. Förster-Schreiber et al (2009) conclude from galaxies in the SINS survey that around 30% of the galaxies at z=1-3 are rotationally supported, but turbulent disks probably indicate they have completed most of their formation process, while another 30% might be galaxy mergers.…”
Section: Kinematicsmentioning
confidence: 99%
“…The velocity fields of galaxies at intermediate redshift (0.4 < z < 0.75) have been investigated using FLAMES/GIRAFFE at VLT Puech et al 2006;Yang et al 2008;Neichel et al 2008;Puech et al 2008). In their sample of 65 galaxies, Yang et al (2008) found about 32% relaxed rotating disks.…”
Section: Introductionmentioning
confidence: 99%
“…Galaxies are selected in different fields by their absolute J band magnitude (M J (AB) < −20.3 -see Ravikumar et al 2007, for more details). A first part of this sample was observed during the FLAMES/GIRAFFE guaranteed time and is described in Flores et al (2006), Puech et al (2006a), Puech et al (2006b), and . The other part was observed in the frame of the large program IMAGES and is described in Yang et al (2007, hereafter Paper I).…”
Section: Introductionmentioning
confidence: 99%